2020
DOI: 10.1007/s00227-019-3630-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term trends in albatross diets in relation to prey availability and breeding success

Abstract: Diet analyses can reveal important changes in seabird foraging ecology and, by inference, resource availability and predator-prey dynamics within the wider marine ecosystem. Here, we analysed stomach contents of 1544 grey-headed albatross Thalassarche chrysostoma (GHA) and black-browed albatross T. melanophris (BBA) chicks from Bird Island, South Georgia. We describe dietary shifts (1996-2017), and link those to annual prey availability indices and breeding success. Annual variability in diet was high, and lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 57 publications
1
16
1
Order By: Relevance
“…Firstly, grey-headed albatrosses may have shifted their diets or foraging habitats to more contaminated prey or regions. Analyses of stomach contents of chicks have revealed a major dietary shift in breeding grey-headed albatrosses at South Georgia since the mid-1990s, including a reduction in the occurrence of the seven-star flying squid ( Martialia hyadesi ) and an increase in mackerel icefish ( Champsocephalus gunnari ) [ 34 ]. However, adults may not consume the same prey that they provision to chicks and, given the difficulties in obtaining samples, the only conventional diet information for grey-headed albatrosses outside of the breeding period is for the cephalopod component [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, grey-headed albatrosses may have shifted their diets or foraging habitats to more contaminated prey or regions. Analyses of stomach contents of chicks have revealed a major dietary shift in breeding grey-headed albatrosses at South Georgia since the mid-1990s, including a reduction in the occurrence of the seven-star flying squid ( Martialia hyadesi ) and an increase in mackerel icefish ( Champsocephalus gunnari ) [ 34 ]. However, adults may not consume the same prey that they provision to chicks and, given the difficulties in obtaining samples, the only conventional diet information for grey-headed albatrosses outside of the breeding period is for the cephalopod component [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between δ 15 N and Hg exposure is often apparent when comparing mean values for different species within seabird communities [ 10 , 15 ], but is less frequently observed within a single species [ 8 ]. That it was apparent in our study population is probably because grey-headed albatrosses at South Georgia consume a wide range of prey from multiple trophic levels [ 34 ], and the variation in δ 15 N values among individuals was very high (range: 8.8–15.2‰).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have examined responses to changing oceanographic conditions of organisms at different trophic levels, or sought to predict the impacts on distributions 22 , 23 . In the Southern Ocean, documented effects of climate variability on ecological processes, include changes in diet, foraging areas, breeding success or abundance, particularly at higher trophic levels, such as in penguins and albatrosses 24 27 . The only such studies on key pelagic zooplankton or nekton are those on krill 28 , 29 .…”
Section: Introductionmentioning
confidence: 99%
“…2006) and is a population‐level generalist (Mills et al . 2020). Two studies analysing geolocator data from a small number of non‐breeding birds revealed that most target the Sub‐Antarctic Zone (SAZ: between the Antarctic Polar Front (APF) and the Subtropical Front (STF)), with evidence for small‐scale sexual segregation and some consistency in habitat use within the same non‐breeding period (Croxall et al .…”
mentioning
confidence: 99%